Social innovation in a Romani community. The case of the Gandhi Secondary School in Hungary - Forray, Katalin R; Kozma, Tamas (Central European Journal of Educational Research, 2026)
T The Story. Following the post-communist transition of 1989–90, a Romani secondary school—the first of its kind in Europe—was established in Pécs, Hungary. This initiative began as a grassroots civic movement and operated under non-governmental management from 1994 to 2011. In 2011, the Hungarian state took over oversight, and the institution was restructured as a non-profit organisation. This study presents and analyses the Gandhi Secondary School as a notable example of social innovation. Research Questions. a) What prompted the surge of civic initiatives within the Romani community of Southern Transdanubia after the political transition? b) How can we explain the trajectory of the Gandhi Secondary School, which experienced initial success, followed by decline, and eventually stabilisation? Methodology. It utilises the framework of educational anthropology. The methodology includes secondary analysis of existing research, participant observation, narrative analysis, and social listening. Results. a) The uniqueness of the Gandhi Secondary School stems from its origin as a social innovation directly emerging from the local and regional Romani community. b) Although its lifecycle aligns with theoretical models of social innovation, its specific ’destiny’ is closely linked to the socio-political context of the post-communist transition. Thus, this lifecycle serves as both a model and a unique historical case. c) The history of this innovation illustrates that in the Hungarian context, social innovations can only be sustained through strong partnerships with central/ local government.